2017
DOI: 10.1186/s13071-017-2115-7
|View full text |Cite
|
Sign up to set email alerts
|

Human-landing rate, gonotrophic cycle length, survivorship, and public health importance of Simulium erythrocephalum in Zaragoza, northeastern Spain

Abstract: Background Simulium (Boophthora) erythrocephalum (De Geer, 1776) is one of the blackfly species responsible for major public health problems in Europe. Blackfly outbreaks of this species are becoming more frequent, threatening public health in Spain. In the present study, bionomic parameters of S. erythrocephalum in northeastern Spain were estimated.Methods Simulium erythrocephalum was collected from May through June 2015 in Zaragoza, Spain, using the human-landing-collection (HLC) method. Daily pattern of tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 21 publications
3
31
0
4
Order By: Relevance
“…The optimal temperature for host-seeking activity of S. erythrocephalum was between 22.17 to 27.35°C in the evening. With regard to solar radiation, blackflies showed host-seeking activity at values below 123.51 W/m 2 (evening hours) with the most intensive host-seeking behaviour at solar radiation of 8 W/m 2 , recorded at 20:30 PM, in conditions of dim sunlight (Ruiz-Arrondo et al 2017). In this context, in our study the first swarm was observed at the illuminance value of 300 lux and the last one at 45 lux.…”
Section: Resultssupporting
confidence: 51%
See 3 more Smart Citations
“…The optimal temperature for host-seeking activity of S. erythrocephalum was between 22.17 to 27.35°C in the evening. With regard to solar radiation, blackflies showed host-seeking activity at values below 123.51 W/m 2 (evening hours) with the most intensive host-seeking behaviour at solar radiation of 8 W/m 2 , recorded at 20:30 PM, in conditions of dim sunlight (Ruiz-Arrondo et al 2017). In this context, in our study the first swarm was observed at the illuminance value of 300 lux and the last one at 45 lux.…”
Section: Resultssupporting
confidence: 51%
“…Also, Peterson (1959), noted that males of Simulium arcticum (Malloch, 1914) (complex of nearctic species) were swarming during the daylight at 14:30 over the headwaters of the Provo River in Utah, USA. According to Ruiz-Arrondo et al (2017), the bimodal daily landing-activity pattern of S. erythrocephalum was affected by temperature and solar radiation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hasta ahora, son escasos los trabajos que han abordado este tema, aunque merece ser reseñado el de Werner (2003), que incluye un repaso de la vegetación de hidrófitos y helófitos del río Oder y sus tributarios en Alemania, como sustrato de otras especies antropófilas. En España, se han realizado varios estudios o informes, sobre diferentes ríos, como son los casos del Ebro y del Henares, que tienen problemas asociados a la proliferación de hidrófitos (13) (14) que pueden afectar a los usos del agua y a la salud ambiental de los ecosistemas acuáticos. Entre estos problemas se incluye la proliferación de dipteros picadores, como es el caso de algunas especies de simúlidos.…”
Section: Palabras Claveunclassified